Combining the uncombinable: corporate memories, ethnobiological observations, oceanographic and ecological data to enhance climatic resilience in small-scale fisheries - Garibay-Toussaint, Isabel; Olguín-Jacobson, Carolina; Woodson, C. Brock; Arafeh-Dalmau, Nur; Torre, Jorge; Fulton, Stuart; Micheli, Fiorenza; O’Connor, Ryan; Précoma-de la Mora, Magdalena; Hernández-Velasco, Arturo; Narchi, Nemer E. (Frontiers in Marine Science, 2024)
Human survival relies on understanding environmental processes and ecological responses to weather changes. The global food production system is increasingly challenged by abrupt and unpredictable weather events, hindering communities' ability to prepare for climate variations. In coastal and marine settings, climatic shocks like marine heatwaves and hypoxia events disrupt ecosystems vital for food security, health, and cultural services. Although meteorological predictions have advanced, challenges remain in making forecasts accessible to communities without the academic background or infrastructure to interpret complex models. Integrating local ecological knowledge (LEK) with scientific data offers a promising approach to enhance climate adaptation and decision-making. This study explores enhancing seasonal climate forecasts by merging corporate memories from fishing cooperatives with LEK to reconstruct ecological baselines. By combining oceanographic, ecological, and ethnographic data, we demonstrate how fishers' observations align with marine heatwave data and ecological shifts. Our approach improves understanding of dynamic climate regimes and underscores the importance of local knowledge in building climate resilience. We introduce ethnobiological calendars, integrating daily observations with oceanographic data, as a tool for proactive environmental management. This method bridges traditional and scientific knowledge, promoting effective natural resource management and resilience building. Our research contributes to developing comprehensive databases merging corporate memories with scientific data, fostering contextually informed observations essential for understanding climate dynamics. By emphasizing the role of local calendars in preserving traditional knowledge and guiding sustainable practices, we advocate for inclusive climate adaptation approaches rooted in community-based insights and experiences. This integration enhances the reliability and utility of seasonal climate forecasts, strengthening resilience strategies against climatic shocks.